Etanercept in the treatment of plaque psoriasis - Thao U Nguyen; John Koo (Dove Medical Press, 2009)
Thao U Nguyen, John KooDepartment of Dermatology, Psoriasis and Skin Treatment Center, University of California, San Francisco, San Francisco, California, USAAbstract: Etanercept is approved for the treatment of moderate to severe plaque psoriasis at a dose of 50 mg twice weekly for 3 months followed by a maintenance dosage of 50 mg weekly thereafter. Clinical studies have shown excellent efficacy, favorable benefit to side-effects ratio, and safe long-term usage. Extensive information on safety is available as etanercept has been used for many years for other indications such as rheumatoid arthritis and psoriatic arthritis and is the first of the tumor necrosis factor antagonists to gain approval in psoriasis.Keywords: etanercept, plaque psoriasis, tumor necrosis factor antagonist